Convergent and divergent learning in photovoltaic pilot projects and subsequent niche development - Barbara van Mierlo (Sustainability: Science, Practice, & Policy, 2012)
A proposed strategy to facilitate the use and development of radical new sustainable technologies is the creation of niches. Learning in these niches and the social embedding of learning experiences can stimulate changes in existing sociotechnological regimes. Pilot projects in which new technologies are used may form part of these niches. This article describes the results of a Dutch research project involving photovoltaics on learning within pilot projects and subsequent actions of the participating parties. The central questions are whether and how internal processes, such as open and creative negotiations, foster learning and how such learning relates to subsequent niche developments.The study suggests that pilot projects could encourage both convergent and divergent learning, depending on whether participants’ learning experiences and expectations of the new technology start to align. Although the two types of learning can coexist, they seem related to different process conditions. The implication of these findings is that the management of pilot projects to contribute to regime change involves strategic choices about stimulating either the opening or the closing of the novelty’s interpretative flexibility.